IMPLEMENTASI KEARIFAN LOKAL DALAM PENEGAKAN HUKUM DI BIDANG KEHUTANAN - Mega Fitri Hertini; Dina Karlina (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study uses a socio-legal approach, which focuses on local wisdom of forest resource management by the community with local legal norms that are actually operated to maintain community order and its implementation in law enforcement. In addition, in this study the authors describe the correlation of national political development with social phenomena that are deeply related to public understanding or public reactions to crimes committed by Forest Tenure Rights (HPH) holders in West Kalimantan. That legal politics and community reactions as the embodiment of local wisdom in law enforcement against crime, essentially starts from the development of public legal awareness of the crimes around them. From the perspective of criminal sociology, that the official reaction of the community as local wisdom and law enforcement is a series of events related to events that occurred previously, namely the occurrence of forest and land fires (Karhutla). The community's reaction shows us how this reaction needs special attention so that what the community does can meet their expectations, in addition to being in line with applicable laws and regulations. The hope of society in general is that peace and welfare are more guaranteed and that crime can be suppressed as low as possible.